Preparation, growth mechanism and slag resistance behavior of ternary Ca2Mg2Al28O46 (C2M2A14). Issue 3 (15th January 2019) - Li, Bin; Chen, Haiyang; Chen, Junhong; Wang, Enhui; Hou, Xinmei; Li, Yong
Abstract: The ternary phase Ca2 Mg2 Al28 O46 (C2 M2 A14 ) in the CaO‐Al2 O3 ‐MgO system was synthesized by reaction sintering using analytically pure CaO, MgO and Al2 O3 as raw materials. The solid‐solution reaction between CaAl12 O19 (CA6 ) and MgAl2 O4 (MA) takes place at 1650°C and hexagonal thick flake C2 M2 A14 are produced at 1750°C. Due to the substitution of Al 3+ for Mg 2+ in the spinel unit of C2 M2 A14, C2 M2 A14, CM2 A8 and CA2 appear in the product batched with stoichiometric ratio. When the firing temperature is 1750°C and the solid soluble amount of Al 3+ is 0.2, C2 M2 A14 with high purity of 96.5 wt % is obtained. As for the growth mechanism, it follows a two‐dimensional nucleation theory, i.e., MA forms two‐dimensional nuclei on the (0001) plane of CA6 and provide growth steps for atomic deposition. When the temperature reaches a certain point, MA's crystallization interface obtains great growth driving force and MA on the layer begins to merge with the CA6 matrix to form hexagonal thick flake C2 M2 A14 . During the slag corrosion, the formation of dense coating layer with CA2 as the main component improve the high temperature stability and corrosion resistance. Therefore, C2 M2 A14 is of great potentiality to be applied in the ladle lining.